Top 10 students who received the Gawad KKK - Outstanding Youth of the Philippines awards - Que, Bryan Christopher Ngo (Animo Repository, 2000)
Bryan Christopher Ngo Que, aa Civil Engineering major and BPI Science Awardee, Rowena Viviene Sy, an Organizational Communication-Marketing major and Student Council President, were named in the list of top 10 students who received the Gawad KKK - Outstanding Youth of the Philippines Awards. The awards were given in a formal ceremony in Marikina City.